Molecular-level effects on cell membrane models to explain the phototoxicity of gold shell-isolated nanoparticles to cancer cells - Camacho, Sabrina A. [UNESP]; Kobal, Mirella B. [UNESP]; Almeida Jr, Alexandre M. [UNESP]; Toledo, Karina A. [UNESP]; Oliveira Jr, Osvaldo N.; Aoki, Pedro H. B. [UNESP] (Elsevier B.V., 2020)
Metallic nanoparticles are promising agents for photothermal cancer therapy (PTT) owing to their photostability and efficient light-to-heat conversion, but their possible aggregation remains an issue. In this paper, we report on the photoinduced heating of gold shell-isolated nanoparticles (AuSHINs) in in vitro experiments to kill human oropharyngeal (HEp-2) and breast (BT-474 and MCF-7) carcinoma cells, with cell viability reducing below 50 % with 2.2 x 10(12) AuSHINs/mL and 6 h of incubation. This toxicity to cancer cells is significantly higher than in previous works with gold nanoparticles. Considering the AuSHINs dimensions we hypothesize that cell uptake is not straightforward, and the mechanism of action involves accumulation on phospholipid membranes as the PTT target for photoinduced heating and subsequent generation of reactive oxygen species (ROS). Using Langmuir monolayers as simplified membrane models, we confirmed that AuSHINs have a larger effect on 1,2-dioleoyl-snglycero-3-phospho-L-serine (DOPS), believed to represent cancer cell membranes, than on 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) taken as representative of healthy eukaryotic cells. In particular, data from polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS) revealed an increased conformational order of DOPS tails due to the stronger adsorption of AuSHINs. Furthermore, light irradiation reduced the stability of AuSHINs containing DOPC and DOPS monolayers owing to oxidative reactions triggered by ROS upon photoinduced heating. Compared to DOPC, DOPS lost nearly twice as much material to the subphase, which is consistent with a higher rate of ROS formation in the vicinity of the DOPS monolayer.
Keywords: Photothermal cancer therapy (PTT); Gold shell-isolated nanoparticles (AuSHINs); Langmuir monolayers